2013
DOI: 10.1289/ehp.1206245
|View full text |Cite|
|
Sign up to set email alerts
|

Roxarsone, Inorganic Arsenic, and Other Arsenic Species in Chicken: A U.S.-Based Market Basket Sample

Abstract: Background: Inorganic arsenic (iAs) causes cancer and possibly other adverse health outcomes. Arsenic-based drugs are permitted in poultry production; however, the contribution of chicken consumption to iAs intake is unknown.Objectives: We sought to characterize the arsenic species profile in chicken meat and estimate bladder and lung cancer risk associated with consuming chicken produced with arsenic-based drugs.Methods: Conventional, antibiotic-free, and organic chicken samples were collected from grocery st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
171
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(183 citation statements)
references
References 24 publications
4
171
1
7
Order By: Relevance
“…Many of these concerns stem from practices common to IFAP, such as the continued use of arsenical drugs in poultry production (110), the use of hormones in beef and dairy production, and the widespread administration of antimicrobials (see the section entitled Antimicrobial Resistance). Animal slaughtering and meat-processing facilities present further multiple opportunities for microbial cross-contamination (77,119), which are heightened by the volume of carcasses and the speed at which they are processed.…”
Section: Microbial and Chemical Contaminationmentioning
confidence: 99%
“…Many of these concerns stem from practices common to IFAP, such as the continued use of arsenical drugs in poultry production (110), the use of hormones in beef and dairy production, and the widespread administration of antimicrobials (see the section entitled Antimicrobial Resistance). Animal slaughtering and meat-processing facilities present further multiple opportunities for microbial cross-contamination (77,119), which are heightened by the volume of carcasses and the speed at which they are processed.…”
Section: Microbial and Chemical Contaminationmentioning
confidence: 99%
“…In fact, according to U S Environmental Protection Agency (EPA 1988), human problems caused by arsenic can be associated with water and fish consumption but rarely to domestic animals or meat. Nevertheless, a recent study by Nachman et al (2013), in samples from chicken breasts for human consumption in the USA, showed that animals with detectable roxarsone (presumably representing treated chicken) had higher inorganic Arsenic concentrations than chicken without detectable roxarsone.…”
Section: Introductionmentioning
confidence: 99%
“…For broilers, two papers were available; one concerned the farm level in Europe (Schiavone et al, 2008), and one the retail level in the USA (Nachman et al, 2013). Schiavone et al (2008) did not find a difference in ochratoxin A concentration in broiler blood and feed.…”
Section: Broilersmentioning
confidence: 99%
“…Schiavone et al (2008) did not find a difference in ochratoxin A concentration in broiler blood and feed. The USA study showed that the level of inorganic arsenic in conventional chicken breasts was significantly higher (p<0.05) than in organic, due to the use of the drug arsenic containing roxarsone, that is licenced for use in the USA but not in the EU, and possibly due to arsenic concentration in drinking water (Nachman et al, 2013).…”
Section: Broilersmentioning
confidence: 99%